2014
DOI: 10.1093/molehr/gau096
|View full text |Cite
|
Sign up to set email alerts
|

Reliable pre-eclampsia pathways based on multiple independent microarray data sets

Abstract: Pre-eclampsia is a multifactorial disorder characterized by heterogeneous clinical manifestations. Gene expression profiling of preeclamptic placenta have provided different and even opposite results, partly due to data compromised by various experimental artefacts. Here we aimed to identify reliable pre-eclampsia-specific pathways using multiple independent microarray data sets. Gene expression data of control and preeclamptic placentas were obtained from Gene Expression Omnibus. Single-sample gene-set enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A publicly accessible microarray data set of IFN-treated cells (GEO accession GSE3920) was downloaded ( Indraccolo et al , 2007 ). Single sample gene set enrichment analysis (ssGSEA) ( Barbie et al , 2009 ) for ‘IFN- γ signature' in GSE3920 and KOV-75 was performed using R, as reported previously ( Kawasaki et al , 2014 ). Briefly, R code for ssGSEA was downloaded from Genepattern ( http://www.broadinstitute.org/cancer/software/genepattern/ ), and gmt file for IFN- γ signature gene symbols and gct file for KOV75 were used as input files and ‘ssGSEA-Projection.Library.R' and ‘common R' were calculated using R.…”
Section: Methodsmentioning
confidence: 99%
“…A publicly accessible microarray data set of IFN-treated cells (GEO accession GSE3920) was downloaded ( Indraccolo et al , 2007 ). Single sample gene set enrichment analysis (ssGSEA) ( Barbie et al , 2009 ) for ‘IFN- γ signature' in GSE3920 and KOV-75 was performed using R, as reported previously ( Kawasaki et al , 2014 ). Briefly, R code for ssGSEA was downloaded from Genepattern ( http://www.broadinstitute.org/cancer/software/genepattern/ ), and gmt file for IFN- γ signature gene symbols and gct file for KOV75 were used as input files and ‘ssGSEA-Projection.Library.R' and ‘common R' were calculated using R.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the maternally expressed imprinted gene CYCLIN-DEPENDENT KINASE INHIBITOR 1C ( CDKN1C ) has variously been reported to be significantly decreased [97], increased [98, 99], or unaltered [100] in preeclamptic placentas. These conflicting results may be explained by a difference in mode of delivery, given recent evidence demonstrating significantly increased CDKN1C expression in laboring versus non-laboring placentas [101].…”
Section: Methodsmentioning
confidence: 99%
“…Although several lines of evidence have suggested that statins exert antioxidant effects by enhancing Nrf2 activation, no study has examined the efficacy of simvastatin on Nrf2 signaling in trophoblast cells . Among the Nrf2 target genes, we focused on HO‐1, GCLC and GCLM, as we found that their mRNA expression levels were decreased in pre‐eclamptic placentas . Overexpression of HO‐1 in endothelial cells results in a significant decrease in the production of soluble fms‐like tyrosine kinase 1 (sFlt‐1), the most important antiangiogenic factor associated with pre‐eclampsia .…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that Nrf2 activation was significantly reduced in pre‐eclamptic compared with normal placentas, and consequently, the messenger ribonucleic acid (mRNA) expression of the target gene HO‐1 was decreased in pre‐eclamptic placentas . In addition, we found that the expressions of other Nrf2 target genes, GCLC and GCLM , were also reduced in pre‐eclamptic placentas . Yet the underlying precise mechanism by which Nrf2 activation is disrupted in pre‐eclamptic placentas still requires elucidation.…”
Section: Introductionmentioning
confidence: 97%